Shrinkage behaviour of kaolin enhanced with superabsorbent polymer - Nor Yusnita, Yaacob (2018)
Huge amount of waste disposal to landfill every single day can cause environmental problem to landfill. Clay can be one of the solution the environmental problem which it can be used for geo-environmental application such as clay barriers, landfill barriers and can act as treatment and waste control. Kaolinite has lower plasticity besides it is locally available and has lower cost compared to a few other types of clay such as bentonite, illite and montmorillonite. Shrinkage behaviour of kaolinite will be studied by applying Clod Test. Enhancement of Super Absorbent Polymer (SAP) can help to improve the performance of shrinkage behaviour of kaolinite as it has high adsorption and retention of fluids. The objectives of this study are to test the shrinkage behaviour of kaolinite enhanced with SAP and to obtain shrinkage curve of void ratio versus water content using Clod Test.